The relevance of spatial aggregation level and of applied methods in the analysis of geographical distribution of cancer mortality in mainland Portugal (2009-2013) - Roquette, Rita (2018)
Roquette, R., Nunes, B., & Painho, M. (2018). The relevance of spatial aggregation level and of applied methods in the analysis of geographical distribution of cancer mortality in mainland Portugal (2009-2013). Population Health Metrics, 16(1), [6]. DOI: 10.1186/s12963-018-0164-6